Empowerment of Society Art Groups as Supporting Magnetism of Sendang Made Natural Tourist Attraction, Jombang Regency - Muhammad Alhada Fuadilah Habib; Binti Khoirun Nisa; Bintis Ti'anatud Diniati; Asik Putri Ayusari Ratnaningsih; Mukhammad Fatkhullah (Budapest International Research and Critics University, 2022)
Sendang Made is a natural tourist attraction in Jombang Regency that has good potential to be developed. The potential is in the form of natural resources, history, culture, and art. Before this empowerment program is conducted, the tourist attraction has not been managed properly. Therefore, the existing potential has not been able to attract tourists. This society empowerment program seeks to optimize existing potential by integrating it into better tourist attraction management. The approach used in this society empowerment program is the ABCD (Asset Based Community Development) approach. The first stage of this society empowerment program is to map the potential possessed by Sendang Made using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. In this first stage, the authors conduct a research process using a qualitative approach as well as data collection techniques using field observation, in-depth interviews, and documentation from literature studies. After mapping the potential of Sendang Made, the second stage is to form a management organization for Sendang Made. The third stage is to conduct socialization and training on the management of the tourist attraction. The fourth stage is to integrate the potential of Sendang Made, especially the artistic potential of the surrounding society. The fifth stage is to help in marketing this tourist attraction through social media. The last stage is to monitor and evaluate the program implementation. With this empowerment program, it is expected to increase the number of tourists that can have an impact on improving the surrounding society's economy